3‐Dimensional simulations and student learning in orthodontic education. (3rd October 2021) - Ho, Angus Cheuk Hin; Liao, Chongshan; Lu, Jiajing; Shan, Zhiyi; Gu, Min; Bridges, Susan M.; Yang, Yanqi
Abstract: Introduction: The electronic dental model (e‐model) is an example of a digital 3‐dimensional technology to support inquiry‐based learning in undergraduate dental education. As student perceptions of and engagement with e‐models vary, it is uncertain whether these perceptions have implications for their learning processes and outcomes. Materials and Methods: Third‐year dental students ( N  = 40) completed a questionnaire to identify their perceptions of and preferences for model modalities. They were divided into three groups based on their preference: Preferring plaster models (Group 1); Preferring e‐models (Group 2); No preference (Group 3). Students from three groups ( N  = 9) attended a hands‐on digital occlusion evaluation workshop, and then completed a case‐based diagnostic evaluation test using digital occlusion evaluation software. Camtasia Studio™ recorded real‐time and on‐screen data of the number of mouse‐clicks and time spent. Results: Students reported positive feedbacks on the use of e‐models, and 72.5% of the students preferred combination use of e‐models and plaster models. After attending the hands‐on digital dental occlusion evaluation workshop, Group 2 scored higher on the diagnostic evaluation test ( p  < .05) and registered more mouse‐clicks than Group 1 when evaluating the arch symmetry ( p  < .05). Group 2 registered fewer mouse‐clicks than Group 3 during tooth size measurement ( p  < .05). There was no significant difference regarding the time used to answer the knowledge questions amongst the three groups. Conclusion: Undergraduate dental students indicated a generally high acceptance of e‐models for their learning in orthodontics, and more prefer a blended approach. Students preferring e‐models presented higher performance outcomes, which supports cognitive load theory regarding prior exposure to simulation‐based environments.